Evaluation of Evaporative Degradation of Arc Torch Cathodes in Hydrocarbon-Containing Plasmas for Spraying, Thermal Protection Testing and Related Technologies - A. V. Gorbunov; V. A. Gorbunova; O. G. Devoino; G. Petraconi Filho; A. A. Halinouski (Наука и техника)
Design of non-transferred DC electric arc plasma torches (EAPTs) operated with plasma gases containing alkane hydrocarbons, as a promising type of heaters for a number of technologies (thermal spraying, surface hardening, testing of thermal protection systems, etc.), requires taking into account the evaporation rate of surface cathode material (as one of the channels of its ablative degradation). For this procedure, as the first stage, thermodynamic methods can be used to simulate the composition and properties of reactive C–H–O–N–Ar–Me-systems with variable set of such input parameters as the ratio of components of plasma-forming mixture, its pressure and temperature. We theoretically estimated the evaporative degradation of the material for three variants of EAPT cathode with alkane-containing plasmas (“hot” thermochemical zirconium and thermionic tungsten, and “cold” copper) in equilibrium and quasi-equilibrium modes of “plasma gas + surface cathode material”-mixture, with use of generalized thermodynamic properties of the materials. The calculation for conditions with pressure, which is characteristic for EAPT discharge chamber, showed that when varying the initial composition of the plasma-forming mixture (from oxidizers (air or combustion products of alkanes) to reducing gases based on the products of combined partial oxidation and pyrolysis of alkanes), the effect of a difference in the cathode evaporation rate EAI was observed in systems based on (air + alkane)-mixtures near the melting point of surface cathode substances, in a comparison with the case of EAPTs with more conventional gases (commercial N2, air) and, importantly, for two variants of the analyzed cathodes (with the exception of copper). In addition, the electrode erosion value was compared for simulated zirconium cathode (in terms of erosion evaporative component) when operating on the combustion products of alkanes from “air + CH4”-mixture, and for some known EAPTs with similar cathodes in other gases. Using the case of earlier tested DC plasma torch with rod Zr-cathode (with microheterogeneous surface) as an example, it was found that our calculation indicates non-monotonic dynamics of EAI value and fractions of Zr-containing vapors as a result of the change of the fuel-air equivalence ratio f of initial reactive mixture. This effect is inconsistent with measured cathode composition, which shows a probability of nonequilibrium character of thermal and diffusion processes in near-electrode plasma and surface layer (~1 mm) of the electrode, at least in the modes with arc current in the torch near 300 A. Besides this, it should be noted that obtained modeling data on the behavior of zirconium compounds (ZrO2, ZrC) in C–H–O–N–Ar–Zr-system can be used not only for improvement of the torch cathodes, but also for design of new Zr-containing thermal protection systems to predict preliminary their ablation rate in a flow of products of combustion (including incomplete one) of engine-, rocket- and other fuels. Similarly, the results on the copper compounds behavior near the metal evaporation temperature can be useful for optimizing the process of plasma spraying of copper alloy coatings.